Contribution to the knowledge of Chinese Cerconychia Klapálek (Plecoptera: Pteronarcyoidea: Styloperlidae) with a new synonym - Zhao, Meng-Yuan; Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2020)
Cerconychia Klapálek, 1913 is a genus of the Asian family Styloperlidae that is included in the superfamily Pteronarcyoidea. The genus currently includes five species that mainly occur southern and northwestern China, with one species also found in Vietnam. We recently examined specimens from Yunnan, Hainan, and Taiwan provinces, China and determined them as C. flectospina Wu 1962, C. sinensis Yang & Yang, 1995, and C brunnea Klapálek, 1913. We place Cerconychia sapa Stark & Sivec, 2007 as a junior subjective synonym of C. flectospina. We provide new images of the three species to facilitate identification.